What is the role of the Constitutional Court in Safe-guarding the separation of powers in a dominant party democracy? - Jaftha, Justin Willian (Department of Public Law, 2019)
This thesis presents an analysis of the effect of dominant party democracy on South Africa’s traditional trilateral structures of government, with emphasis on the Constitutional Court. A dominant party democracy brings with it negative features, such as the blurring of boundaries of state and party, and the capturing of important institutions. In South Africa, it is specifically the capture of various independent institutions (state capture) by a dominant party and the placing of its members into these institutions to remove effective checks on the exercise of power by the government, which have been a worrying trend recently. This, in turn, spells rough weather ahead for our constitutional democracy, because it has the effect of withering down the effective system of checks and balances as part of the separation of powers doctrine in South Africa.The central question to explore in this thesis is thus. how the Constitutional Court can protect the democratic space by acknowledging the challenges posed by one-party dominance to democratic institutions and developing doctrines/strategies to deal with this, while not overstepping the mark and infringing on the separation of powers. This is not an easy task for the Constitutional Court to get exactly right. Thus, the Constitutional Court of South Africa has been widely criticised for avoiding any formal confrontation with the current government during its early years. Critics focused on cases such as the UDM floor crossing case and Glenister I. These two decisions have come under attack from constitutional law scholars, who labelled the Constitutional Court as a constrained court and argued that the court was not sufficiently pro-active in confronting the challenges of a dominant party democracy directly. This has led some scholars to the view that the South African Constitutional Court needs to develop a well thought through theory of the threat posed by the dominant party to the quality of South Africa’s democracy. The argument is that there may be a need for the South African Constitutional Court to develop a formal jurisprudence to deal with the negative consequences of a dominant party democracy. In this thesis, I will argue that this critique against the South African Constitutional Court seems out-of-date and, to some extent, overdone. The Constitutional Court in recent years has altered its approach and now deals differently (and more effectively) with the problems posed by dominant party democracy. This is evident from recent decisions such as the UDM secret ballot and two EFF judgments and the Glenister II judgment. In my view, the Constitutional Court has become more forceful in protecting the democratic space in South Africa because of changing political circumstances and because of the weakening position and complex, and sometimes contradictory, responses 8 from the ruling party in South Africa. At the same time, the Constitutional Court has acted with appropriate deference, addressing problems associated with one-party dominance while also showing adequate respect for the separation of powers doctrine. By adopting this approach, and if one views the Constitutional Court’s role through the lens of dominant party democracy, South African democracy – and South Africans themselves – have been better off. If the Court had taken a more forceful approach, it would have placed itself on a direct collision course with the ANC. That might have put the Court’s very existence at risk, and our hard-fought democracy.